Pesquisa de alterações genéticas em pacientes com Transtorno do Espectro Autista (TEA) em uma amostra de Minas Gerais, Brasil: uma avaliação genético-molecular - Michele da Silva Gonçalves (2019)
Autistic Spectrum Disorder (ASD) is a neurodevelopmental disorder characterized by impairment of social interaction and communication associated with repetitive behaviors and stereotypies. The TEA presents a broad spectrum of phenotypic variation when considering the degree of commitment and limitations imposed on the affected person and his / her family. In addition, comorbidities are frequent, such as epilepsy, speech and language disorders, and intellectual disability. Some forms are characterized by behavioral regression. The condition is multifactorial, with several causes already identified, such as exposure to pollutants, infections during pregnancy, maternal diseases. Genetic causes are identified in a fraction of the patients, including chromosomal changes (trisomy and translocations), submicroscopic alterations (microdeletions and microduplications) and monogenic disorders (Fragile X syndrome, among many others). Over the last decades, the frequency of TEA has increased, reaching 1 to 2% in several populations. This increase in frequency has justified several systematic studies, seeking to characterize the contribution of different types of etiologies in different populations. Research and identification of genetic abnormalities may contribute to an improved flow of diagnosis and potentially influence therapeutic approaches. No similar study was conducted in the population of the state of Minas Gerais. The objective of this study was to investigate the contribution of some genetic disorders to the etiology of ASD in a sample of patients from a child psychiatry service under regular monitoring in a tertiary hospital in Minas Gerais. It is therefore a crosssectional study with a convenience sample. The diagnosis of ASD was performed by a child psychiatrist based on clinical criteria of DSM-IV/V and ICD-10. Clinical and demographic data were obtained through medical record research and structured interviews with parents or guardians. The genetic tests were performed staggered in the following order: karyotype, screening for expansive mutations in FMR1 (Fragile X Syndrome) and detection of microdeletions and specific microduplications using the SALSA MLPA P245-B1 and SALSA MLPA P343-C2 kits. In the karyotype with Gbandage, at least 20 cells were analyzed in the resolution of 400 to 450 bands. Molecular research on Fragile X Syndrome was based on the determination of the number of CGG repeats in the FMR1 gene. In the study of deletions and duplications, the SALSA MLPA P245-B1 kits were used to screen for genetic syndromes that may be associated with TEA and the MLPA P343-C2 SALSA kit to evaluate specific TEArelated chromosomal regions. We analyzed 65 samples of children and adolescents aged 2 to 17 years (mean age 10 ± 3.21 years), being 80% male. The mean gestational age was 38 ± 2.86 weeks, being 13.8% preterm and 10.9% with low birth weight. Other more frequent clinical findings were history of fetal distress, neonatal jaundice and epilepsy. The mean maternal age at birth was 29 ± 8.62 years. Pre-eclampsia was reported in gestation of nine patients (13.8%) and gestational diabetes in three. The frequency of preeclampsia in our sample was greater than that of the general population, a condition already associated with an increased risk of autism. Dysmorphism, detected by analysis of photographs, were present in 25 (40%) of 62 patients. No numerical and structural changes were detected to the karyotype. One (1.5%) of 65 patients had Fragile X Syndrome. Two patients had a molecular diagnosis established with the SALSA MLPA P245-B1 kit, a 15q24 deletion present in one male patient, and another 22q13 deletion present in a female patient. This latter change was also detected by the SALSA MLPA P343-C2 kit. In addition, two questionable results were obtained with the